Pine Wilt Disease: a threat to European forestry - Vicente, Cláudia (2012)
Bursaphelenchus xylophilus, the pinewood nematode (PWN) and causal agent of Pine Wilt Disease (PWD), was detected for the first time, in 1999, in Portugal, and in Europe. Despite the efforts of the Portuguese National Forestry and Quarantine Authorities, the disease has spread to new forest areas in the centre of mainland Portugal, in 2008, and to the island of Madeira, in 2009. More recently, two foci of PWD were reported from Spain. The free circulation of non-treated wood and wood products, as part of global trade, may explain this phenomenon, which constitutes a threat to other European forestlands. This review gathers the most recent upto-date information about PWD in Europe, as well as in other countries, presenting integrative management procedures for detection and control, and the scientific knowledge generated over the last decade, to understand the complex biological system behind the disease.